The Roman past in the consciousness of the Roman elites in the ninth and tenth centuries - West-Harling, V (De Gruyter, 2018)
Pope Leo placed a crown on his head, and he was hailed by the whole Roman people: To the august Charles, crowned by God, the great and peaceful emperor of the Romans, life and victory! After the acclamations the pope addressed him in the manner of the old emperors. The name of Patricius was now abandoned and he was called Emperor and Augustus.¹